The Toxin–Antidote Model of Cytoplasmic Incompatibility: Genetics and Evolutionary Implications. Issue 3 (March 2019) - Beckmann, John F.; Bonneau, Manon; Chen, Hongli; Hochstrasser, Mark; Poinsot, Denis; Merçot, Hervé; Weill, Mylène; Sicard, Mathieu; Charlat, Sylvain
Abstract : Wolbachia bacteria inhabit the cells of about half of all arthropod species, an unparalleled success stemming in large part from selfish invasive strategies. Cytoplasmic incompatibility (CI), whereby the symbiont makes itself essential to embryo viability, is the most common of these and constitutes a promising weapon against vector-borne diseases. After decades of theoretical and experimental struggle, major recent advances have been made toward a molecular understanding of this phenomenon. As pieces of the puzzle come together, from yeast and Drosophila fly transgenesis to CI diversity patterns in natural mosquito populations, it becomes clearer than ever that the CI induction and rescue stem from a toxin–antidote (TA) system. Further, the tight association of the CI genes with prophages provides clues to the possible evolutionary origin of this phenomenon and the levels of selection at play. Highlights: Wolbachia are maternally inherited intracellular bacteria of many Arthropod species. They can invade populations through various strategies including CI, whereby the symbionts protect eggs from the lethal effect of the sperm of infected males. It has long been proposed that this phenomenon may rely on a toxin deposited by the bacterium before its elimination from maturing sperm, and on an antidote that is provided in an infected egg by the maternal symbiont. Recent research toward the molecular basis of CI has turned the spotlight on two syntenic loci in a prophage region which recapitulate the CI phenotype and are organized in a typical TA fashion. This genetic architecture, that is archetypal of TA systems that promote the spread of selfish mobile elements in free-living bacteria, provides clues to the possible evolutionary origin of CI.